Slovak Republic : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2003)
Slovakia is now one of the fastest-growing EU accession countries. Despite the upswing, the Slovak economy remains hampered by structural weaknesses and related macroeconomic imbalances. Over the medium term, IMF staff believes that Slovakia should aim for an external current account deficit under 5 percent GDP. However, all agreed that additional measures will be needed to reach the deficit target. The authorities' strategy remains to achieve medium-term fiscal consolidation through expenditure reduction, but they acknowledged that a more explicit expenditure policy was needed.